Factors associated with non-participation and drop-out in a lifestyle intervention for workers with an elevated risk of cardiovascular disease - van der Beek Allard J; Proper Karin I; Groeneveld Iris F; Hildebrandt Vincent H; van Mechelen Willem (BMC, 2009)
Abstract Background Non-response and drop-out are problems that are commonly encountered in health promotion trials. Understanding the health-related characteristics of non-participants and drop-outs and the reasons for non-participation and drop-out may be beneficial for future intervention trials. Methods Male construction workers with an elevated risk of cardiovascular disease (CVD) were invited to participate in a lifestyle intervention study. In order to investigate the associations between participation and CVD risk factors, and drop-out and CVD risk factors, crude and multiple logistic regression analyses were performed. The reasons for non-participation and drop-out were assessed qualitatively. Results 20% of the workers who were invited decided to participate; 8.6% of the participants dropped out before the first follow-up measurement. The main reasons for non-participation were 'no interest', 'current (para-)medical treatment', and 'feeling healthy', and for drop-out they were 'lack of motivation', 'current (para-)medical treatment', and 'disappointment'. Participants were 4.2 years older, had a higher blood pressure, higher total cholesterol, and lower HDL cholesterol than non-participants, and were more likely to report 'tiredness and/or stress' and 'chest pain and/or shortness of breath'. After adjusting for age, most risk factors were not significantly associated with participation. Drop-outs were 4.6 years younger than those who completed the study. The prevalence of smoking was higher among non-participants and drop-outs. Conclusion Participants had a worse CVD risk profile than non-participants, mainly because of the difference in age. Non-participants and drop-outs were younger and more likely to be smokers. The main reasons for non-participation and drop-out were health-related. Investigators in the field of health promotion should be encouraged to share comparable information. Trial registration Current Controlled Trials ISRCTN60545588